CPWF Volta V3 Main Message Poster - CGIAR Challenge Program on Water and Food (CGIAR Challenge Program on Water and Food, 2013)
Trade-offs between agricultural intensification and the health status of aquatic ecosystems have to be thoroughly considered in order to ensure the sustainability of these socio-eco-agro-ecosystems.